China's Muslims and Japan's Empire : Centering Islam in World War II - Hammond, Kelly A. (Islamic civilization & Muslim networks., 2020)
"In this transnational history of World War II, Kelly A. Hammond places Sino-Muslims at the center of imperial Japan's challenges to Chinese nation-building efforts. Revealing the little known story of Japan's interest in Islam during its occupation of North China, Hammond shows how Japanese aimed to defeat Chinese Nationalists in winning the hearts and minds of Sino-Muslims, a vital minority population. Offering programs that presented themselves as benevolent protectors of Islam, the Japanese aimed to provide Muslims with a viable alternative-and, at the same time, to create new Muslim consumer markets that would, in Japan's vision, help to subvert the existing global capitalist world order and destabilize the Soviets"--